Leadership Model to Increase Employee Motivation and Discipline - Komar Priatna, Deden; Mulyana, Agus; Jusdijachlan, Jusdijachlan; Roswinna, Winna; Ridwan, S.; Suryani, Herni; Limakrisna, Nandan (Green Publisher, 2023)
The goal of this research is to analyze how Leadership and Work Motivation impact Work Discipline. Conducted through explanatory quantitative research in thirty manufacturing companies based in DKI Jakarta with a sample size of eighty respondents, the study employed the SEM-PLS approach. The findings indicate that Leadership has a direct effect on Work Discipline in manufacturing companies located in DKI Jakarta, while Work Motivation also directly influences Work Discipline in the same companies.